COST ACCOUNTING FOR SERVICE COMPANY - Ramdan Padmakusumah, Rizal (International Journal of Psychosocial Rehabilitation, 2020)
Cost information is very important for all types of companies. Cost information is basically generated by financial accounting in general, but detailed cost information is only conveyed by cost accounting. This study aims to open thinking about the opportunities for the use of cost accounting in service companies in the form of private universities. The sample of this research is 8 (eight) private universities in the City of Bandung. Research conducted is qualitative research with secondary data as the main data source. The analysis method used is descriptive-qualitative. The results showed that the costs at the private university can be classified into types of variable costs, semi-variable costs, semi-fixed costs, and fixed costs. Costs at private universities are mostly in the type of semi-variable costs and fixed costs. The suggestion from this study is that private universities, in addition to using financial accounting, also need to use cost accounting together to produce cost reports in more detail, which will be very useful for the purposes of analysis and decision-making. The academic advice from this research is that in order to determine or classify costs more accurately, it is necessary to approach the quantitative cost behavior analysis.